Childhood cancer survivorship : improving care and quality of life - National Cancer Policy Board (U.S.); Hewitt, Maria Elizabeth; Weiner, Susan Lipschitz, 1942-; Simone, Joseph V.; Institute of Medicine (U.S.); National Research Council (U.S.) (Washington, D.C. : National Academies Press, 2003)
Commissioned by the National Cancer Policy Board, the nine chapters in this report explore the medical, social, and economic consequences of surviving childhood cancer, identify essential elements of quality care, assess the status of applied clinical and health services research, and propose policies to improve the quality of life for childhood cancer survivors and their families. No index is provided. Annotation : 2004 Book News, Inc., Portland, OR (booknews.com).
The Epidemiology of Childhood Cancer -- The Trajectory of Childhood Cancer Care -- Late Effects of Childhood Cancer -- Delivering Survivorship Care -- Assuring Appropriate Educational Support Services -- Employment, Insurance, and Economic Issues -- Research Issues -- Findings and Recommendations.
Includes bibliographical references.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Tumors in children -- Complications; Tumors in children -- Patients -- Services for; Tumors in children -- Government policy -- United States; Children; Victims; Medical policy; Needs assessment; Statistics; Neoplasms; Child; Neoplasms -- Child; Survivors; Follow-Up Studies; Health Policy; Needs Assessment; Tumeurs chez l'enfant -- Complications et séquelles.; Tumeurs chez l'enfant -- Politique gouvernementale -- États-Unis.; Enfants; Victimes; Politique sanitaire; Analyse des besoins; children (people by age group); needs assessment; HEALTH & FITNESS -- Children's Health; Victims; Needs assessment; Medical policy; Children; United States; Statistics; Statistics; Statistics; Statistics; Statistiques